Muscle metabolism and whole blood amino acid profile in patients with liver disease. (17th November 2015) - Dam, Gitte; Sørensen, Michael; Buhl, Mads; Sandahl, Thomas D.; Møller, Niels; Ott, Peter; Vilstrup, Hendrik
Abstract : Objective . Branched-chain amino acids (BCAA) are used in liver cirrhosis to promote protein synthesis, support ammonia detoxification, and treat hepatic encephalopathy. Cirrhosis leads to subnormal BCAA plasma concentrations and studies indicate that levels are decreased due to their role in muscle ammonia removal. Muscle contribution has not been fully elucidated. We studied muscle amino acid metabolism in six healthy subjects, 13 cirrhosis patients and six patients with an episode of alcoholic hepatitis. Methods . Subjects had catheters inserted into the femoral artery and vein to obtain arterial (A) and venous (V) concentrations of amino acids (μmol/L blood). Results . BCAA concentrations were lower in patients with cirrhosis compared to healthy subjects ( p < 0.05) with no difference between patients with alcoholic hepatitis and the other groups. Muscle BCAA uptake was variable and on average higher in patients with alcoholic hepatitis and patients with stable cirrhosis compared to healthy subjects (mean A-V difference 0.5 and 32 vs. − 12 μmol/L blood) ( p = 0.22). The release of aromatic amino acids (AAA) was comparable in the three groups ( P > 0.30). The BCAA/AAA (Fischer's ratio) was lower in patients with cirrhosis and patients with alcoholic hepatitis compared to healthy subjects (mean 1.65, 1.17 and 2.73, both p < 0.05) and it was negatively correlated to the Child-Pugh score ( p < 0.05). Conclusions . Patients with liver disease have lower BCAA and higher AAA blood concentrations compared to healthy subjects. The trend towards an increased muscle uptake of BCAA may have contributed but this was not significant.